Proceedings of the 17th International Conference on World Wide Web 2008
DOI: 10.1145/1367497.1367589
|View full text |Cite
|
Sign up to set email alerts
|

Tag-based social interest discovery

Abstract: The success and popularity of social network systems, such as del.icio.us, Facebook, MySpace, and YouTube, have generated many interesting and challenging problems to the research community. Among others, discovering social interests shared by groups of users is very important because it helps to connect people with common interests and encourages people to contribute and share more contents. The main challenge to solving this problem comes from the difficulty of detecting and representing the interest of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
161
0
10

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 269 publications
(176 citation statements)
references
References 12 publications
5
161
0
10
Order By: Relevance
“…Previous studies have already shown that tags cannot only improve the search effectiveness (Heymann, Koutrika, & Garcia-Molina, 2008;Xu, Bao, Fei, Su, & Yu, 2008), but also support knowledge discovery (Li, Guo, & Zhao, 2008). Schenkel et al (2008) rank top-k results looking at social and semantic dimensions.…”
Section: Discussion and Related Workmentioning
confidence: 98%
“…Previous studies have already shown that tags cannot only improve the search effectiveness (Heymann, Koutrika, & Garcia-Molina, 2008;Xu, Bao, Fei, Su, & Yu, 2008), but also support knowledge discovery (Li, Guo, & Zhao, 2008). Schenkel et al (2008) rank top-k results looking at social and semantic dimensions.…”
Section: Discussion and Related Workmentioning
confidence: 98%
“…This latter considers the tags as the users interests [9,23]. We compare the result provided by our approach with the result of the approach that uses all the tags of the neighbours (without considering their relevance to the associated resources).…”
Section: Evaluation According To Tag-based Approachmentioning
confidence: 99%
“…While their mechanism develops a logical context data model and a physical data store, our mechanism deals with the concrete challenges of making such type of protection feasible, without relying on third parties' verification or auditing. Concerning policy propagation based on folksonomies, our work builds on related approaches on customization and personalization of tag-based information retrieval [12], [19], [14]. Several techniques involved in exploring social annotations include association rule mining [14] and EM-based probabilistic learning approach [12], [19], [24].…”
Section: Related Workmentioning
confidence: 99%
“…Concerning policy propagation based on folksonomies, our work builds on related approaches on customization and personalization of tag-based information retrieval [12], [19], [14]. Several techniques involved in exploring social annotations include association rule mining [14] and EM-based probabilistic learning approach [12], [19], [24].…”
Section: Related Workmentioning
confidence: 99%